Nilai-Nilai Kepemimpinan Dan Kewirausahaan Sayyidah Khadijah: Kajian Literatur Tokoh Muslimah - Nia, Naila Amanyya Muhibin; Ashif Az Zafi (STIKes Ibnu Sina Ajibarang, 2025)
Sayyidah Khadijah bint Khuwailid was a very influential figure in Islamic history, recognized as the first wife of the Prophet Muhammad SAW and the first woman to accept Islam. She was an intelligent person, had a far-sighted vision, came from a family with good financial conditions, and was known for her integrity and high morality. The purpose of this research is to explore the leadership principles and entrepreneurial qualities exhibited by Sayyidah Khadijah bint Khuwailid, an influential woman in Islamic history, who was characterized by her intelligence, her support for the mission of the Prophet Muhammad SAW, and her implementation of ethical business practices. This study uses a qualitative approach through literature analysis, which investigates various sources from classical to modern texts. The findings show that Sayyidah Khadijah developed a visionary and strategic leadership style, seen in her ability to manage her business and choose the right partners. She also implemented solid Islamic business principles, known as